Automotive Vocational High School: How Career Guidance and Parents Support Impact the Students’ Work Readiness - Purnawan, Purnawan; Santosa, Budi; Kurniawan, Arief; Hakim, Ananda Rizky (Universitas Ahmad Dahlan, 2020)
This study aims to determine the contributions of career guidance and parents support to the vocational high school students' work readiness. This research is survey. The sampling technique used a proportional random sampling method. The data collection used the questionnaire method to obtain career guidance data, support parents, and students’ work readiness. The data analysis included descriptive analysis, prerequisite analysis including normality test, linearity test, and multi-collinearity test, and multiple analysis with F-test, determination test, and partial correlation analysis. The results showed that (1) career guidance and parents’ support influenced positively and significantly to work readiness of vocational students, (2) career guidance influenced positively and significantly to work readiness of students in vocational school, and (3) the parental support influenced positively and significantly on work readiness of students in vocational high schools.